The CMD: A comparative dataset on parliamentary committee membership in 14 countries - Jens Wäckerle; Bruno Castanho Silva; Danielle Pullan; Firuze Taner (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
Cross-national parliamentary data have increasingly enabled scholars to study the behavior of individual Members of Parliament (MPs), allowing insights into issues such as (re)selection, intra-party dissent, and representation. Yet data on MPs' activity have largely been limited to speeches, roll-call votes, and bill sponsorship. We introduce the Committee Membership Dataset (CMD), a major expansion of available legislative data. The CMD records all committee assignments for MPs in 14 countries (14,963 MPs in 260 parties) from 1989 to 2024, including positions held (e.g., member, chairperson), assignment dates, and committee policy areas. Harmonized MP and party identifiers allow linkage with other widely used datasets. We illustrate the CMD's value by showing that women are systematically underrepresented in prestigious committees and chairperson roles across all 14 countries. These disparities persist across nearly all party families. The CMD provides a new resource for analyzing legislative behavior, institutional power, and political representation across democracies.
Keywords: D72; 330; Committee positions; parliaments; political careers; dataset; political science